1999
DOI: 10.1007/bf02482319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of various anticancer agents on intestinal anastomosis after intraperitoneal administration

Abstract: In this study, the effects of intraperitoneal 5-fluorouracil (5-FU), cisplatinum (Cis), adriamycin (Adr), and methotrexate (MTX) administration on rat intestinal anastomosis were compared. Cis and MTX led to significant weight loss in the first 5 days compared with the control group. Within 14 days all rats except the MTX group nearly reached their preoperative weight. No remarkable weight loss or systemic toxicity was observed among the 5-FU and Adr groups. The anastomosis bursting pressure (ABP) at 1 week wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Arikan et al reported the detrimental effects of cisplatinum on intestinal anastomoses in a model similar to ours. 32 Thus, we must examine the differences between cisplatinum and its analogue OX carefully. Shirafuji et al suggested that the depletion of macrophages in the anastomotic site is a major cause of impaired wound healing in bronchial anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Arikan et al reported the detrimental effects of cisplatinum on intestinal anastomoses in a model similar to ours. 32 Thus, we must examine the differences between cisplatinum and its analogue OX carefully. Shirafuji et al suggested that the depletion of macrophages in the anastomotic site is a major cause of impaired wound healing in bronchial anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients on active chemotherapy are subjected to major surgery even though chemotherapy impairs wound healing. 4,5,7,[11][12][13] Adriamycin is a broadspectrum anthracycline group chemotherapeutic agent widely used in cancer treatment. 14,15 However, it has many side effects; most notably, it is cardiotoxic, it can cause congestive cardiac insufficiency, it has a doserelated myelosuppressive effect, and it is locally toxic to the tissues, causing ulceration and necrosis if it extravasates out of vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of this drug are well documented and although the mechanism of impaired wound healing is understood, the exact interval of this impairment is uncertain. [2][3][4][5][6][7] The observation times in previous studies were short and different periods of wound healing were evaluated. Therefore, we evaluated the effect of adriamycin on wound healing in the long term when surgery was performed at different time points during this period, to determine the optimal timing for surgery after adriamycin treatment.…”
Section: Introductionmentioning
confidence: 99%